2003
DOI: 10.1002/ajh.10348
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelators for the treatment of iron overload disease: Relationship between structure, redox activity, and toxicity

Abstract: The success of the iron (Fe) chelator desferrioxamine (DFO) in the treatment of ␤-thalassemia is limited by its lack of bioavailability. The design and characterization of synthetic alternatives to DFO has attracted much scientific interest and has led to the discovery of orally active chelators that can remove pathological Fe deposits. However, chelators that access intracellular Fe pools can be toxic by either inhibiting Fe-containing enzymes or promoting Fe-mediated free radical damage. Interestingly, toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 153 publications
5
123
0
1
Order By: Relevance
“…Here, in lieu of PGC-1 overexpression, we treated the cells with deferoxamine (DFO), a clinically used cell-permeable iron chelator (Chaston and Richardson, 2003). Strikingly, the microarray results revealed that DFO treatment strongly diminished the abundance of mitochondrial transcripts ( Figure 1D).…”
Section: Iron Chelation Causes a Pervasive Dampening Of Mitochondrialmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, in lieu of PGC-1 overexpression, we treated the cells with deferoxamine (DFO), a clinically used cell-permeable iron chelator (Chaston and Richardson, 2003). Strikingly, the microarray results revealed that DFO treatment strongly diminished the abundance of mitochondrial transcripts ( Figure 1D).…”
Section: Iron Chelation Causes a Pervasive Dampening Of Mitochondrialmentioning
confidence: 99%
“…DFO is a well-characterized and clinically used iron chelator (Chaston and Richardson, 2003); nonetheless, to ensure that our observed effects are not an off-target effect of this drug, we deprived cells of iron through two additional mechanisms. First, we depleted cellular iron stores by overexpressing the iron exporter ferroportin (Nemeth et al, 2004) in human embryonic kidney (HEK) 293 cells (one of the lines tested in Figure 2D).…”
Section: Iron-dependent Mitochondrial Restructuring Is Distinct From mentioning
confidence: 99%
“…Ocular toxicity is, however, not directly related to the desferrioxamine dose, serum ferritin level, or total blood transfused. Desferrioxamine toxicity is thought to arise secondary to chelation of metals, such as iron, copper, zinc, cobalt, and nickel, which are essential for normal retinal function [5,7,10,11]. In particular, copper fluxes induced by desferrioxamine may induce retinal toxicity by oxidative cell membrane damage, interrupting monoaminergic neurotransmission in the retina, impairing antioxidant synthesis, and promoting oxidative enzyme reactions in the retina [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, the decompartamentalization of Fe would lead to the expansion of the LIP and the increase of the oxidative damage. In the second case, it has been described an increase in Fe levels in the substantia nigra of Parkinsonian brains [5], Hallervorden-Spatz syndrome [6] and in mitochondria of Friedrich´s ataxia cerebella [7]. Hereditary hemochromatosis is a very common genetic defect in the Caucasian population, with an autosomal recessive inheritance.…”
Section: Introductionmentioning
confidence: 99%